High-strength crosslinked polyethylene power cable and preparation method and application thereof
Patent Information
- Application Number
- CN202611205694.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]有鉴于此,本申请提供一种高强交联聚乙烯电力电缆及其制备方法与应用,该高强交联聚乙烯电力电缆通过乙烯基硅烷交联体系与多维多尺度增强填料的协同作用,实现了高强度与高韧性的统一、刚性增强与抗应力开裂的统一、短期力学性能与长期耐久性的统一,解决了传统聚乙烯外护套抗拉强度不足、纤维增强界面结合力弱、非交联体系长期服役蠕变失效等行业共性难题,产品力学性能突出、耐磨抗冲击、耐环境应力开裂性能优异,制备工艺可控
[0040]本申请提供的高强交联聚乙烯电力电缆实现了高强度与高韧性兼顾、刚性增强与抗应力开裂统一、短期力学性能与长期耐久性同步提升的深度协同,有效应对了传统聚乙烯外护套抗拉强度不足、纤维增强界面脱粘、非交联体系长期蠕变失效的问题。相较于现有技术,该高强交联聚乙烯电力电缆具有拉伸强度高、断裂伸长率大、耐磨抗冲击、耐环境应力开裂性能优异的特点,同时兼具制备工艺可控、可规模化量产的优势,能够满足矿山、港口机械、大跨距架空输电及牵引供电等复杂工况下的高强度使用需求,具备突出的实用价值与产业化应用潜力。
Abstract
Description
Technical Field
[0001] This application relates to the field of power cable technology, and in particular to a high-strength cross-linked polyethylene power cable, its preparation method, and its application. Background Technology
[0002] Cross-linked polyethylene (XLPE) power cables are key foundational equipment in power transmission and distribution systems and electrified transportation, playing an irreplaceable role in ensuring the safe operation of the power grid and the reliability of traction power supply. With the continuous expansion of applications in mining, port machinery, long-span overhead power transmission, and high-speed railway traction power supply, the laying and operating environments of cables are becoming increasingly complex and demanding, placing higher requirements on the mechanical strength of the cables. However, existing XLPE power cables generally suffer from insufficient mechanical properties of the outer sheath, with tensile strength typically only 20-30 MPa and limited elongation at break. In actual laying and use, cables must withstand various complex mechanical loads such as dragging, bending, torsion, heavy object crushing, and soil and rock compression. Especially in mine roadways, shafts, and frequently moved power supply equipment, the outer sheath is highly susceptible to scratches, cracks, necking, and even breakage. According to relevant engineering statistics, non-electrical faults caused by mechanical damage to the outer sheath account for more than 40% of all faults in cables operating under harsh conditions, significantly shortening cable lifespan and seriously affecting the safety and reliability of the power supply system.
[0003] Using high-density polyethylene (HDPE) or increasing the thickness of the outer sheath are traditional techniques for improving the mechanical properties of cables. HDPE has high rigidity and hardness, which can enhance the tensile and compressive strength of the outer sheath to a certain extent. However, HDPE alone has inherent defects such as poor toughness and high notch sensitivity. It is prone to stress cracking at low temperatures and brittle fracture when the bending radius is too large, making it difficult to meet the comprehensive mechanical performance requirements under complex working conditions. Simply increasing the sheath thickness can compensate for insufficient strength to some extent, but it will lead to an increase in the overall weight of the cable, a decrease in bending performance, and difficulties in construction and laying. At the same time, it will reduce the current carrying capacity of the cable due to the deterioration of heat dissipation performance. At present, the industry has also tried to modify and reinforce the polyethylene outer sheath by adding inorganic fillers and chopped fibers. However, inorganic fillers generally have poor compatibility with the polyethylene matrix interface, uneven dispersion, and are prone to stress concentration points, resulting in a significant decrease in material toughness. Although fiber reinforcement can improve tensile strength, traditional fibers have strong surface inertness and weak bonding with the matrix. Under long-term external force, the fibers are easy to be pulled out or debonded, and the reinforcement effect is significantly reduced.
[0004] To address the aforementioned technical shortcomings, there is an urgent need to improve existing technologies. Summary of the Invention
[0005] In view of this, this application provides a high-strength cross-linked polyethylene power cable, its preparation method and application. This high-strength cross-linked polyethylene power cable achieves a balance between high strength and high toughness, rigidity enhancement and stress crack resistance, and short-term mechanical properties and long-term durability through the synergistic effect of the vinyl silane cross-linking system and multi-dimensional and multi-scale reinforcing fillers. It solves common industry problems such as insufficient tensile strength of traditional polyethylene outer sheath, weak interfacial bonding of fiber reinforcement, and creep failure of non-cross-linked systems during long-term service. The product has outstanding mechanical properties, excellent wear resistance, impact resistance, and environmental stress crack resistance, and the preparation process is controllable.
[0006] In the first aspect, this application provides a high-strength cross-linked polyethylene power cable, the technical solution of which is as follows:
[0007] A high-strength cross-linked polyethylene power cable includes a conductor, a cross-linked polyethylene insulation layer extruded over the conductor, and an outer sheath extruded over the cross-linked polyethylene insulation layer. The outer sheath, by weight, comprises the following raw materials:
[0008] 50-70 parts high-density polyethylene, 15-30 parts linear low-density polyethylene, 8-15 parts modified basalt fiber, 5-10 parts nano-silica hybrid particles, 5-8 parts modified calcium carbonate whiskers, 2-4 parts vinyltrimethoxysilane, 0.8-1.5 parts dicumyl peroxide, 3-6 parts maleic anhydride-grafted polyethylene, 0.3-0.8 parts pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 0.5-1 parts silicone masterbatch;
[0009] The high-density polyethylene has a melt index of 0.5~2.0 g / 10 min and a density of 0.945~0.955 g / cm³. 3 The linear low-density polyethylene has a melt index of 0.5~3.0 g / 10 min and a density of 0.918~0.925 g / cm³. 3 .
[0010] Optionally, the method for preparing the modified basalt fiber includes the following steps:
[0011] Basalt fiber chopped strands and an aqueous solution of γ-glycidyl etheroxypropyltrimethoxysilane were mixed and coupled to obtain the initial modified fiber.
[0012] The modified basalt fiber is obtained by mixing the pre-modified fiber with an aqueous polyurethane emulsion and then coating it.
[0013] Optionally, the mass-to-volume ratio of the basalt fiber chopped strands and the aqueous solution of γ-glycidoxypropyltrimethoxysilane is 1 g: (8~15) mL, and the mass concentration of the aqueous solution of γ-glycidoxypropyltrimethoxysilane is 1%~3%.
[0014] Optionally, the diameter of the basalt fiber short filaments is 5~15μm and the length is 1~3mm.
[0015] Optionally, the coupling treatment is carried out under stirring conditions, wherein the stirring speed is 200~400 r / min, the temperature is 50~60℃, and the time is 1~2 h.
[0016] Optionally, the mass-to-volume ratio of the modified fiber to the aqueous polyurethane emulsion is 1 g: (3~6) mL, and the solid content of the aqueous polyurethane emulsion is 10%~20%.
[0017] Optionally, the coating treatment is performed at a temperature of 25-35°C for 20-40 minutes.
[0018] Optionally, the method for preparing the nano-silica hybrid particles includes the following steps:
[0019] Nano-silica, γ-methacryloxypropyltrimethoxysilane and toluene were mixed and then silanized under a nitrogen protective atmosphere to obtain functionalized nano-silica.
[0020] The functionalized nano-silica, methyl methacrylate monomer, azobisisobutyronitrile and toluene are mixed and grafted under a nitrogen protective atmosphere to obtain the nano-silica hybrid particles.
[0021] Optionally, the mass-to-volume ratio of the nano-silica, γ-methacryloyloxypropyltrimethoxysilane and toluene is 1 g: (0.15~0.25) g: (10~20) mL.
[0022] Optionally, the particle size of the nano-silica is 15~30nm.
[0023] Optionally, the silanization treatment is carried out under stirring conditions, wherein the stirring speed is 200~400 r / min, the temperature is 70~90℃, and the time is 3~5 h.
[0024] Optionally, the mass-volume ratio of the functionalized nano-silica, methyl methacrylate monomer, azobisisobutyronitrile and toluene is 1 g: (0.8~1.5) g: (0.01~0.03) g: (8~15) mL.
[0025] Optionally, the grafting treatment is carried out under stirring conditions, wherein the stirring speed is 200~400 r / min, the temperature is 65~75℃, and the time is 4~6 h.
[0026] Optionally, the method for preparing the modified calcium carbonate whiskers includes the following steps:
[0027] Modified calcium carbonate whiskers are obtained by mixing calcium carbonate whiskers, titanate coupling agent, stearic acid and isopropanol and then modifying them.
[0028] Optionally, the calcium carbonate whiskers have a diameter of 0.5~2μm and an aspect ratio of 15~30.
[0029] Optionally, the mass-to-volume ratio of the calcium carbonate whiskers, titanate coupling agent, stearic acid and isopropanol is 1 g: (0.01~0.03) g: (0.005~0.02) g: (5~10) mL.
[0030] Optionally, the modification treatment is carried out under stirring conditions, wherein the stirring speed is 200~400 r / min, the temperature is 40~50℃, and the time is 1~2 h.
[0031] Secondly, this application provides a method for preparing the high-strength cross-linked polyethylene power cable described in the aforementioned scheme, comprising the following steps:
[0032] The conductors are stranded together, and a cross-linked polyethylene insulation layer is extruded outside the conductors to perform cross-linking, thus obtaining the primary cable;
[0033] High-density polyethylene, linear low-density polyethylene, modified basalt fiber, nano-silica hybrid particles, modified calcium carbonate whiskers, maleic anhydride-grafted polyethylene, vinyltrimethoxysilane, dicumyl peroxide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and silicone masterbatch are mixed and then subjected to a mixing treatment to obtain a mixture.
[0034] The mixture is melted and granulated using a twin-screw extruder, and then extruded over the insulation layer using a single-screw extruder to form an outer sheath. After cross-linking treatment, a high-strength cross-linked polyethylene power cable is obtained.
[0035] Optionally, the mixing process is carried out under stirring conditions, wherein the stirring speed is 500~800 r / min, the temperature is 60~80℃, and the time is 15~25 min.
[0036] Optionally, the temperature of each zone of the twin-screw extruder is 150~180℃, and the screw speed is 100~200rpm.
[0037] Optionally, the temperature of each zone of the single-screw extruder is 140~165℃, the die temperature is 155~165℃, and the screw speed is 15~30r / min.
[0038] Optionally, the crosslinking treatment is performed at a temperature of 85-95°C for 8-16 hours.
[0039] Thirdly, this application provides the application of the high-strength cross-linked polyethylene power cable described in the aforementioned scheme in the field of traction power supply.
[0040] The high-strength cross-linked polyethylene power cable provided in this application achieves a deep synergy, balancing high strength and high toughness, unified rigidity enhancement and stress crack resistance, and simultaneous improvement in short-term mechanical properties and long-term durability. It effectively addresses the problems of insufficient tensile strength of traditional polyethylene outer sheaths, fiber reinforcement interface debonding, and long-term creep failure in non-cross-linked systems. Compared to existing technologies, this high-strength cross-linked polyethylene power cable features high tensile strength, large elongation at break, excellent wear and impact resistance, and superior resistance to environmental stress cracking. It also boasts the advantages of controllable manufacturing processes and large-scale mass production, meeting the high-strength requirements of complex operating conditions such as mining, port machinery, long-span overhead power transmission, and traction power supply. It possesses outstanding practical value and industrial application potential. Detailed Implementation
[0041] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. In addition, it should be understood that the specific implementation methods described herein are only for illustration and explanation of this application and are not intended to limit this application.
[0042] In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in its actual use or operating state; while "inner" and "outer" refer to the outline of the device. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative purposes and do not impose numerical requirements or establish an order.
[0043] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.
[0044] In this application, "at least one" means one or more, and "more than one" means two or more. "One or more", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0045] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.
[0046] In the first aspect, this application provides a high-strength cross-linked polyethylene power cable, the technical solution of which is as follows:
[0047] A high-strength cross-linked polyethylene power cable includes a conductor, a cross-linked polyethylene insulation layer extruded over the conductor, and an outer sheath extruded over the cross-linked polyethylene insulation layer. The outer sheath, by weight, comprises the following raw materials:
[0048] 50-70 parts high-density polyethylene, 15-30 parts linear low-density polyethylene, 8-15 parts modified basalt fiber, 5-10 parts nano-silica hybrid particles, 5-8 parts modified calcium carbonate whiskers, 2-4 parts vinyltrimethoxysilane, 0.8-1.5 parts dicumyl peroxide, 3-6 parts maleic anhydride-grafted polyethylene, 0.3-0.8 parts pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 0.5-1 parts silicone masterbatch;
[0049] The high-density polyethylene has a melt index of 0.5~2.0 g / 10 min and a density of 0.945~0.955 g / cm³. 3 The linear low-density polyethylene has a melt index of 0.5~3.0 g / 10 min and a density of 0.918~0.925 g / cm³. 3 .
[0050] This application uses a dual-matrix system composed of high-density polyethylene (HDPE) and linear low-density polyethylene (LDPE). HDPE serves as the main matrix, providing the necessary rigidity and compressive strength for the outer sheath. LDPE, as the toughening component, contains short branches in its molecular chain, effectively absorbing and dissipating stress concentration under external forces, thus improving the flexibility and stress crack resistance of the outer sheath. Both components form a three-dimensional cross-linked network under the action of vinyltrimethoxysilane and dicumyl peroxide, with the molecular chains connected by siloxane bridges, significantly enhancing the material's creep resistance and long-term durability. The two matrices exhibit similar flow characteristics in the molten state, ensuring blending uniformity and processing stability, while also considering the strength, toughness, and extrusion processing performance of the outer sheath.
[0051] This application uses vinyltrimethoxysilane and dicumyl peroxide to construct a silane crosslinking system. Dicumyl peroxide acts as an initiator, decomposing under the high-temperature shear conditions of a twin-screw extruder to generate free radicals. These free radicals initiate a grafting reaction between the double bonds of vinyltrimethoxysilane and the polyethylene molecular chain, introducing silane groups into the side chains of the polyethylene molecular chain. After extrusion molding, crosslinking treatment is performed at 85-95°C. The methoxy groups on the silane groups hydrolyze to generate silanols, and the silanols on adjacent molecular chains condense to form Si-O-Si crosslinking bridges, connecting the linear polyethylene molecular chains into a three-dimensional crosslinked network structure. This three-dimensional crosslinked network endows the outer sheath with creep resistance, environmental stress cracking resistance, and long-term mechanical stability. Simultaneously, the silane crosslinking reaction is mild and controllable, avoiding the material degradation and yellowing problems that may occur during the high-temperature crosslinking process of the peroxide crosslinking system.
[0052] This application uses pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant. This hindered phenolic antioxidant molecule contains four hindered phenolic functional groups, enabling it to efficiently capture free radicals generated by thermo-oxidative processes during high-temperature processing and use of the polyethylene matrix, preventing free radical chain degradation reactions and improving the thermo-oxidative stability and long-term service life of the outer sheath. Compared to general-purpose hindered phenolic antioxidants, it has a larger molecular weight and lower migration, allowing it to remain stably within the outer sheath for extended periods without migration loss.
[0053] This application uses silicone masterbatch as a lubricant. During melt extrusion, the silicone masterbatch can migrate to the space between the melt and the extruder screw, barrel, and die metal walls, forming a low surface energy lubricating interface layer. This effectively reduces the melt viscosity and processing torque of the high-filler system, improving melt flowability and extrusion surface quality. Simultaneously, the polysiloxane component in the silicone masterbatch can gradually migrate to the surface after the sheath is formed, forming a nanoscale lubricating film. This enhances the wear resistance and scratch resistance of the outer sheath surface, meeting the requirements for high-strength outer sheaths.
[0054] In some embodiments, the method for preparing the modified basalt fiber includes the following steps:
[0055] Basalt fiber chopped strands and an aqueous solution of γ-glycidyl etheroxypropyltrimethoxysilane were mixed and coupled to obtain the initial modified fiber.
[0056] The modified basalt fiber is obtained by mixing the pre-modified fiber with an aqueous polyurethane emulsion and then coating it.
[0057] In some embodiments, the mass-to-volume ratio of the basalt fiber chopped strands to the aqueous solution of γ-glycidoxypropyltrimethoxysilane is 1 g: (8~15) mL, and the mass concentration of the aqueous solution of γ-glycidoxypropyltrimethoxysilane is 1%~3%. This ratio ensures that γ-glycidoxypropyltrimethoxysilane forms a uniform monolayer chemical bond on the fiber surface. If the concentration is too low, the coupling will be insufficient; if the concentration is too high, the silane molecules will undergo self-condensation to form oligomers that deposit on the fiber surface, which will reduce the interfacial bonding effect.
[0058] In some embodiments, the basalt fiber chopped strands have a diameter of 5-15 μm and a length of 1-3 mm. The diameter and length of the basalt fiber are key parameters affecting its reinforcing effect and processing performance. A diameter of 5-15 μm ensures that the fiber has a high specific surface area and good flexibility, while a length of 1-3 mm can meet the dispersion requirements of extrusion processing and the fiber bridging reinforcement effect. If the length is too short, the bridging effect is poor; if the length is too long, extrusion dispersion is difficult, and fiber entanglement and screen clogging are likely to occur.
[0059] In some embodiments, the coupling treatment is carried out under stirring conditions, with a stirring speed of 200-400 r / min, a temperature of 50-60°C, and a time of 1-2 h. These coupling conditions enable the complete hydrolysis and condensation reaction of γ-glycidoxypropyltrimethoxysilane on the fiber surface at a mild temperature. If the temperature is too low, the coupling reaction rate is slow and the coupling efficiency is low; if the temperature is too high, the stability of the silane hydrolysate decreases, and silane self-condensation may occur.
[0060] In some embodiments, the mass-to-volume ratio of the initially modified fiber to the aqueous polyurethane emulsion is 1 g: (3~6) mL, and the solid content of the aqueous polyurethane emulsion is 10%~20%. This ratio ensures that the aqueous polyurethane forms a uniform coating layer of appropriate thickness on the fiber surface. If the coating layer is too thin, the interface buffering effect is poor; if it is too thick, the load transfer efficiency between the fiber and the matrix decreases.
[0061] In some embodiments, the coating treatment is performed at a temperature of 25-35°C for 20-40 minutes. This coating condition is carried out at room temperature, allowing the aqueous polyurethane emulsion to be uniformly deposited on the surface of the coupled fiber through physical adsorption and hydrogen bonding. The moderate temperature prevents excessively rapid evaporation of moisture, which could lead to an uneven coating layer.
[0062] In some embodiments, the method for preparing the nano-silica hybrid particles includes the following steps:
[0063] Nano-silica, γ-methacryloxypropyltrimethoxysilane and toluene were mixed and then silanized under a nitrogen protective atmosphere to obtain functionalized nano-silica.
[0064] The functionalized nano-silica, methyl methacrylate monomer, azobisisobutyronitrile and toluene are mixed and grafted under a nitrogen protective atmosphere to obtain the nano-silica hybrid particles.
[0065] In some embodiments, the mass-to-volume ratio of the nano-silica, γ-methacryloxypropyltrimethoxysilane, and toluene is 1 g : (0.15~0.25) g : (10~20) mL. This ratio ensures that γ-methacryloxypropyltrimethoxysilane forms complete surface chemical modification on the nano-silica surface, introducing an appropriate amount of vinyl double bond functional groups. If the amount of silane is too low, the modification density will be insufficient; if the amount of silane is too high, silane self-condensation may occur, leading to particle aggregation.
[0066] In some embodiments, the particle size of the nano-silica is 15-30 nm. This particle size range ensures that the nano-silica has a high specific surface area and surface activity, while avoiding dispersion difficulties and severe agglomeration between particles caused by excessively small particle size.
[0067] In some embodiments, the silanization treatment is carried out under stirring conditions, with a stirring speed of 200-400 r / min, a temperature of 70-90°C, and a time of 3-5 h. This silanization condition is performed near the toluene reflux temperature, allowing the methoxy group of γ-methacryloyloxypropyltrimethoxysilane to fully condense with the silanol groups on the surface of nano-silica, forming stable covalent grafts.
[0068] In some embodiments, the mass-to-volume ratio of the functionalized nano-silica, methyl methacrylate monomer, azobisisobutyronitrile (AIBN), and toluene is 1 g : (0.8~1.5) g : (0.01~0.03) g : (8~15) mL. In this ratio, the amount of methyl methacrylate monomer controls the length of the grafted chain, and AIBN acts as an initiator to control the grafting reaction rate and grafting density, ensuring the formation of a polymethyl methacrylate grafted layer of appropriate thickness on the surface of the nano-silica.
[0069] In some embodiments, the grafting treatment is carried out under stirred conditions, with a stirring speed of 200-400 r / min, a temperature of 65-75°C, and a time of 4-6 h. These grafting conditions are conducted above the decomposition temperature of azobisisobutyronitrile (AIBN), ensuring the initiator continuously and uniformly decomposes to generate free radicals, thus maintaining a stable polymerization rate. If the temperature is too high, the initiator decomposes too quickly, resulting in uneven graft chain length; if the time is too short, the monomer conversion rate is low, and the grafting amount is insufficient.
[0070] In some embodiments, the method for preparing the modified calcium carbonate whiskers includes the following steps:
[0071] Modified calcium carbonate whiskers are obtained by mixing calcium carbonate whiskers, titanate coupling agent, stearic acid and isopropanol and then modifying them.
[0072] In some embodiments, the calcium carbonate whiskers have a diameter of 0.5–2 μm and an aspect ratio of 15–30. The diameter and aspect ratio of calcium carbonate whiskers are key parameters affecting their reinforcing effect. A diameter of 0.5–2 μm falls within the micrometer-level reinforcement range, while an aspect ratio of 15–30 ensures that the whiskers have sufficient bridging length, dissipating fracture energy during crack propagation through whisker pull-out and bridging mechanisms.
[0073] In some embodiments, the mass-to-volume ratio of the calcium carbonate whiskers, titanate coupling agent, stearic acid, and isopropanol is 1 g : (0.01~0.03) g : (0.005~0.02) g : (5~10) mL. In this ratio, the titanate coupling agent provides chemical bonding modification, and stearic acid provides surface hydrophobic modification; the two work synergistically, while isopropanol acts as a dispersion medium to ensure uniform distribution of the modifier on the whisker surface.
[0074] In some embodiments, the modification treatment is carried out under stirring conditions, with a stirring speed of 200-400 r / min, a temperature of 40-50°C, and a time of 1-2 h. These modification conditions allow the modifier to be fully adsorbed and reacted on the whisker surface at a mild temperature. Excessive temperature will cause the isopropanol to evaporate too quickly, affecting the uniformity of the modification; insufficient time will result in an incomplete modification reaction.
[0075] Secondly, this application provides a method for preparing the high-strength cross-linked polyethylene power cable described in the aforementioned scheme, comprising the following steps:
[0076] The conductors are stranded together, and a cross-linked polyethylene insulation layer is extruded outside the conductors to perform cross-linking, thus obtaining the primary cable;
[0077] High-density polyethylene, linear low-density polyethylene, modified basalt fiber, nano-silica hybrid particles, modified calcium carbonate whiskers, maleic anhydride-grafted polyethylene, vinyltrimethoxysilane, dicumyl peroxide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and silicone masterbatch are mixed and then subjected to a mixing treatment to obtain a mixture.
[0078] The mixture is melted and granulated using a twin-screw extruder, and then extruded over the insulation layer using a single-screw extruder to form an outer sheath. After cross-linking treatment, a high-strength cross-linked polyethylene power cable is obtained.
[0079] The preparation method provided in this application involves uniformly mixing the components under conditions below the decomposition temperature of dicumyl peroxide, allowing vinyltrimethoxysilane and dicumyl peroxide to be fully adsorbed onto the surface of polyethylene particles and between the reinforcing fillers. Then, the mixture is melt-granulated at 150-180°C using a twin-screw extruder. This temperature is higher than the decomposition temperature of dicumyl peroxide, where the decomposition of dicumyl peroxide generates free radicals that initiate the grafting of vinyltrimethoxysilane onto the polyethylene molecular chain. Simultaneously, this temperature is lower than the silane condensation crosslinking temperature, preventing crosslinking reactions during the granulation stage from affecting subsequent extrusion molding. Next, the mixture is extruded outside the insulation layer of the primary cable using a single-screw extruder to form an outer sheath. Finally, a crosslinking treatment is performed at 85-95°C, where the methoxy groups on the silane grafted chains hydrolyze to generate silanols, and adjacent silanols condense to form Si-O-Si crosslinking bridges, transforming the linear polyethylene molecular chain into a three-dimensional crosslinked network. This preparation method separates grafting and crosslinking. Grafting is completed but crosslinking is not performed during the granulation stage, which ensures good processing flowability and storage stability of the granules. Crosslinking is then performed after molding, which ensures the molding quality and crosslinking uniformity of the outer sheath.
[0080] In some embodiments, the mixing process is carried out under stirring conditions, wherein the stirring speed is 500~800 r / min, the temperature is 60~80℃, and the time is 15~25 min.
[0081] In some embodiments, the temperature of each zone of the twin-screw extruder is 150~180°C, and the screw speed is 100~200 rpm.
[0082] In some embodiments, the temperature of each zone of the single-screw extruder is 140~165℃, the die temperature is 155~165℃, and the screw speed is 15~30 r / min.
[0083] In some embodiments, the crosslinking treatment is performed at a temperature of 85-95°C for 8-16 hours.
[0084] Thirdly, this application provides the application of the high-strength cross-linked polyethylene power cable described in the aforementioned scheme in the field of traction power supply.
[0085] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.
[0086] Example 1
[0087] This embodiment provides a method for preparing a high-strength cross-linked polyethylene power cable, comprising the following steps:
[0088] Copper conductors are stranded together, and a cross-linked polyethylene insulation layer is extruded on the outside of the conductors. The insulation layer is then cross-linked in hot water at 90°C for 12 hours to obtain a primary cable.
[0089] 600g of high-density polyethylene (melt index 1.2g / 10min, density 0.950g / cm³) was tested. 3 220g linear low-density polyethylene (melt index 1.8g / 10min, density 0.920g / cm³) 3 120g of modified basalt fiber, 80g of nano-silica hybrid particles, 60g of modified calcium carbonate whiskers, 40g of maleic anhydride-grafted polyethylene, 30g of vinyltrimethoxysilane, 12g of dicumyl peroxide, 5g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 8g of silicone masterbatch were mixed and then subjected to a mixing treatment at 650r / min and 70℃ for 20min to obtain a mixture.
[0090] The mixture is melt-granulated using a twin-screw extruder with zone temperatures of 160 / 165 / 170 / 170 / 165°C and a screw speed of 150 rpm. Then, an outer sheath is formed by extruding the primary cable's insulation layer using a single-screw extruder with zone temperatures of 145 / 150 / 155 / 155°C, a die temperature of 160°C, and a screw speed of 20 r / min. Finally, it undergoes cross-linking treatment in 90°C hot water for 12 hours to obtain a high-strength cross-linked polyethylene power cable.
[0091] The method for preparing the modified basalt fiber includes the following steps:
[0092] 100g of basalt fiber short filaments (10μm in diameter and 2mm in length) were mixed with 1200mL of γ-glycidoxypropyltrimethoxysilane aqueous solution (2% by mass). The mixture was stirred at 300r / min and 55℃ for 1.5h for coupling treatment, filtered, and dried at 60℃ to obtain the initial modified fiber.
[0093] The modified fiber was mixed with 450 mL of waterborne polyurethane emulsion (solid content of 15%), and then soaked in the mixture at 30°C for 30 min for coating treatment. After removal, it was dried at 70°C to obtain modified basalt fiber.
[0094] The preparation method of the nano-silica hybrid particles includes the following steps:
[0095] 100g of nano-silica (particle size 20nm), 20g of γ-methacryloxypropyltrimethoxysilane and 1500mL of toluene were mixed and stirred at 300r / min and 80℃ for 4h under nitrogen protection. After centrifugation, the mixture was washed with toluene and dried at 60℃ to obtain functionalized nano-silica.
[0096] 100g of the functionalized nano-silica, 120g of methyl methacrylate monomer, 2g of azobisisobutyronitrile and 1200mL of toluene were mixed and grafted under nitrogen protection at 300r / min and 70℃ for 5h. After precipitation with methanol, washing and drying at 60℃, nano-silica hybrid particles were obtained.
[0097] The method for preparing the modified calcium carbonate whiskers includes the following steps:
[0098] 100g of calcium carbonate whiskers (diameter 1μm, aspect ratio 22), 2g of titanate coupling agent, 1g of stearic acid and 800mL of isopropanol were mixed and stirred at 300r / min and 45℃ for 1.5h for modification treatment. After filtration, washing with isopropanol and drying at 60℃, modified calcium carbonate whiskers were obtained.
[0099] Example 2
[0100] This embodiment provides a method for preparing a high-strength cross-linked polyethylene power cable, comprising the following steps:
[0101] Copper conductors are stranded together, and a cross-linked polyethylene insulation layer is extruded on the outside of the conductors. The insulation layer is then cross-linked in hot water at 85°C for 16 hours to obtain a primary cable.
[0102] 700g of high-density polyethylene (melt index 0.8g / 10min, density 0.953g / cm³) was tested. 3 150g linear low-density polyethylene (melt index 1.2g / 10min, density 0.922g / cm³) 3 100g of modified basalt fiber, 60g of nano-silica hybrid particles, 70g of modified calcium carbonate whiskers, 50g of maleic anhydride-grafted polyethylene, 35g of vinyltrimethoxysilane, 14g of dicumyl peroxide, 6g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 7g of silicone masterbatch were mixed and then subjected to a mixing treatment at 550r / min and 65℃ for 22min to obtain a mixture.
[0103] The mixture is melt-granulated using a twin-screw extruder with zone temperatures of 155 / 160 / 165 / 165 / 160°C and a screw speed of 120 rpm. Then, an outer sheath is formed by extruding the primary cable's insulation layer using a single-screw extruder with zone temperatures of 140 / 145 / 150 / 150°C, a die temperature of 155°C, and a screw speed of 18 r / min. Finally, it undergoes cross-linking treatment in 88°C hot water for 14 hours to obtain a high-strength cross-linked polyethylene power cable.
[0104] The method for preparing the modified basalt fiber includes the following steps:
[0105] 100g of basalt fiber short filaments (8μm in diameter and 1.5mm in length) and 1000mL of γ-glycidyl etheroxypropyltrimethoxysilane aqueous solution (mass concentration of 1.5%) were mixed and coupled at 200r / min and 50℃ for 2h. After filtration, the mixture was dried at 60℃ to obtain the initial modified fiber.
[0106] The modified fiber was mixed with 350 mL of waterborne polyurethane emulsion (solid content of 12%), and then soaked in the mixture at 25°C for 35 min for coating treatment. After removal, it was dried at 65°C to obtain modified basalt fiber.
[0107] The preparation method of the nano-silica hybrid particles includes the following steps:
[0108] 100g of nano-silica (particle size 15nm), 18g of γ-methacryloxypropyltrimethoxysilane and 1200mL of toluene were mixed and stirred at 250r / min and 75℃ for 4.5h under nitrogen protection. After centrifugation, the mixture was washed with toluene and dried at 60℃ to obtain functionalized nano-silica.
[0109] 100g of the functionalized nano-silica, 100g of methyl methacrylate monomer, 1.5g of azobisisobutyronitrile and 1000mL of toluene were mixed and grafted under nitrogen atmosphere at 250r / min and 68℃ for 5.5h. After precipitation with methanol, washing and drying at 60℃, nano-silica hybrid particles were obtained.
[0110] The method for preparing the modified calcium carbonate whiskers includes the following steps:
[0111] 100g of calcium carbonate whiskers (0.8μm in diameter, aspect ratio 18), 1.5g of titanate coupling agent, 0.8g of stearic acid and 600mL of isopropanol were mixed and stirred at 250r / min and 42℃ for 2h for modification treatment. After filtration, washing with isopropanol and drying at 60℃, modified calcium carbonate whiskers were obtained.
[0112] Example 3
[0113] This embodiment provides a method for preparing a high-strength cross-linked polyethylene power cable, comprising the following steps:
[0114] Copper conductors are stranded together, and a cross-linked polyethylene insulation layer is extruded on the outside of the conductors. The insulation layer is then cross-linked in hot water at 95°C for 10 hours to obtain a primary cable.
[0115] 500g of high-density polyethylene (melt index 1.6g / 10min, density 0.948g / cm³) was tested. 3 300g linear low-density polyethylene (melt index 2.5g / 10min, density 0.919g / cm³) 3 140g of modified basalt fiber, 90g of nano-silica hybrid particles, 50g of modified calcium carbonate whiskers, 35g of maleic anhydride-grafted polyethylene, 25g of vinyltrimethoxysilane, 10g of dicumyl peroxide, 4g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 9g of silicone masterbatch were mixed and then subjected to a mixing treatment at 750r / min and 75℃ for 18min to obtain a mixture.
[0116] The mixture is melt-granulated using a twin-screw extruder with zone temperatures of 165 / 170 / 175 / 175 / 170°C and a screw speed of 180 rpm. Then, an outer sheath is formed by extruding the primary cable's insulation layer using a single-screw extruder with zone temperatures of 150 / 155 / 160 / 160°C, a die temperature of 162°C, and a screw speed of 22 r / min. Finally, it undergoes cross-linking treatment in 92°C hot water for 10 hours to obtain a high-strength cross-linked polyethylene power cable.
[0117] The method for preparing the modified basalt fiber includes the following steps:
[0118] 100g of basalt fiber short filaments (diameter 12μm, length 2.5mm) and 1400mL of γ-glycidoxypropyltrimethoxysilane aqueous solution (mass concentration 2.5%) were mixed and coupled under stirring at 350r / min and 58℃ for 1.5h, filtered, and dried at 60℃ to obtain the initial modified fiber;
[0119] The modified fiber was mixed with 500 mL of waterborne polyurethane emulsion (solid content of 18%), and then soaked in the mixture at 32°C for 25 min for coating treatment. After removal, it was dried at 75°C to obtain modified basalt fiber.
[0120] The preparation method of the nano-silica hybrid particles includes the following steps:
[0121] 100g of nano-silica (particle size 22nm), 22g of γ-methacryloxypropyltrimethoxysilane and 1600mL of toluene were mixed and stirred at 350r / min and 85℃ for 3.5h under nitrogen protection. After centrifugation, washing with toluene and drying at 60℃, functionalized nano-silica was obtained.
[0122] 100g of the functionalized nano-silica, 130g of methyl methacrylate monomer, 2.5g of azobisisobutyronitrile and 1300mL of toluene were mixed and grafted under a nitrogen atmosphere at 350r / min and 72℃ for 4.5h. After precipitation with methanol, washing and drying at 60℃, nano-silica hybrid particles were obtained.
[0123] The method for preparing the modified calcium carbonate whiskers includes the following steps:
[0124] 100g of calcium carbonate whiskers (diameter 1.5μm, aspect ratio 25), 2.5g of titanate coupling agent, 1.5g of stearic acid and 900mL of isopropanol were mixed and stirred at 350r / min and 48℃ for 1.5h for modification treatment. After filtration, washing with isopropanol and drying at 60℃, modified calcium carbonate whiskers were obtained.
[0125] Example 4
[0126] This embodiment provides a method for preparing a high-strength cross-linked polyethylene power cable, comprising the following steps:
[0127] Copper conductors are stranded together, and a cross-linked polyethylene insulation layer is extruded on the outside of the conductors. The insulation layer is then cross-linked in hot water at 90°C for 12 hours to obtain a primary cable.
[0128] 650g of high-density polyethylene (melt index 1.0g / 10min, density 0.952g / cm³) was used. 3 200g linear low-density polyethylene (melt index 1.5g / 10min, density 0.921g / cm³) 3 150g of modified basalt fiber, 50g of nano-silica hybrid particles, 80g of modified calcium carbonate whiskers, 60g of maleic anhydride-grafted polyethylene, 32g of vinyltrimethoxysilane, 13g of dicumyl peroxide, 7g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 5g of silicone masterbatch were mixed and then subjected to a mixing treatment at 600r / min and 68℃ for 25min to obtain a mixture.
[0129] The mixture is melt-granulated using a twin-screw extruder with zone temperatures of 158 / 163 / 168 / 168 / 163°C and a screw speed of 140 rpm. Then, an outer sheath is formed by extruding the primary cable's insulation layer using a single-screw extruder with zone temperatures of 148 / 153 / 158 / 158°C, a die temperature of 158°C, and a screw speed of 25 r / min. Finally, it undergoes cross-linking treatment in 90°C hot water for 12 hours to obtain a high-strength cross-linked polyethylene power cable.
[0130] The method for preparing the modified basalt fiber includes the following steps:
[0131] 100g of basalt fiber short filaments (5μm in diameter and 1mm in length) were mixed with 800mL of γ-glycidoxypropyltrimethoxysilane aqueous solution (1% by mass). The mixture was stirred at 250r / min and 52℃ for 2h for coupling treatment, filtered, and dried at 60℃ to obtain the initial modified fiber.
[0132] The modified fiber was mixed with 300 mL of waterborne polyurethane emulsion (solid content of 10%), and then soaked in the mixture at 28°C for 40 min for coating treatment. After removal, it was dried at 60°C to obtain modified basalt fiber.
[0133] The preparation method of the nano-silica hybrid particles includes the following steps:
[0134] 100g of nano-silica (particle size 18nm), 15g of γ-methacryloxypropyltrimethoxysilane and 1000mL of toluene were mixed and stirred at 200r / min and 70℃ for 5h under nitrogen protection. After centrifugation, the mixture was washed with toluene and dried at 60℃ to obtain functionalized nano-silica.
[0135] 100g of the functionalized nano-silica, 80g of methyl methacrylate monomer, 1g of azobisisobutyronitrile and 800mL of toluene were mixed and grafted under a nitrogen atmosphere at 200r / min and 65℃ for 6h. After precipitation with methanol, washing and drying at 60℃, nano-silica hybrid particles were obtained.
[0136] The method for preparing the modified calcium carbonate whiskers includes the following steps:
[0137] 100g of calcium carbonate whiskers (0.5μm in diameter, aspect ratio 15), 1g of titanate coupling agent, 0.5g of stearic acid and 500mL of isopropanol were mixed and stirred at 200r / min and 40℃ for 2h for modification treatment. After filtration, washing with isopropanol and drying at 60℃, modified calcium carbonate whiskers were obtained.
[0138] Example 5
[0139] This embodiment provides a method for preparing a high-strength cross-linked polyethylene power cable, comprising the following steps:
[0140] Copper conductors are stranded together, and a cross-linked polyethylene insulation layer is extruded on the outside of the conductors. The insulation layer is then cross-linked in hot water at 90°C for 12 hours to obtain a primary cable.
[0141] 550g of high-density polyethylene (melt index 1.8g / 10min, density 0.946g / cm³) was tested. 3 250g linear low-density polyethylene (melt index 2.8g / 10min, density 0.918g / cm³) 3 80g of modified basalt fiber, 100g of nano-silica hybrid particles, 60g of modified calcium carbonate whiskers, 45g of maleic anhydride-grafted polyethylene, 28g of vinyltrimethoxysilane, 11g of dicumyl peroxide, 5g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 8g of silicone masterbatch were mixed and then subjected to a mixing treatment at 700r / min and 72℃ for 20min to obtain a mixture.
[0142] The mixture is melt-granulated using a twin-screw extruder with zone temperatures of 162 / 167 / 172 / 172 / 167°C and a screw speed of 160 rpm. Then, an outer sheath is formed by extruding the primary cable's insulation layer using a single-screw extruder with zone temperatures of 142 / 148 / 153 / 153°C, a die temperature of 157°C, and a screw speed of 28 r / min. Finally, it undergoes cross-linking treatment in 90°C hot water for 12 hours to obtain a high-strength cross-linked polyethylene power cable.
[0143] The method for preparing the modified basalt fiber includes the following steps:
[0144] 100g of basalt fiber short filaments (15μm in diameter and 3mm in length) were mixed with 1500mL of γ-glycidoxypropyltrimethoxysilane aqueous solution (3% by mass). The mixture was stirred at 400r / min and 60℃ for 1h for coupling treatment, filtered, and dried at 60℃ to obtain the initial modified fiber.
[0145] The modified fiber was mixed with 600 mL of waterborne polyurethane emulsion (solid content of 20%), and then soaked in the mixture at 35°C for 20 min for coating treatment. After removal, it was dried at 80°C to obtain modified basalt fiber.
[0146] The preparation method of the nano-silica hybrid particles includes the following steps:
[0147] 100g of nano-silica (particle size 25nm), 25g of γ-methacryloxypropyltrimethoxysilane and 2000mL of toluene were mixed and stirred at 400r / min and 90℃ for 3h under nitrogen protection. After centrifugation, the mixture was washed with toluene and dried at 60℃ to obtain functionalized nano-silica.
[0148] 100g of the functionalized nano-silica, 150g of methyl methacrylate monomer, 3g of azobisisobutyronitrile and 1500mL of toluene were mixed and grafted under nitrogen protection at 400r / min and 75℃ for 4h. After precipitation with methanol, washing and drying at 60℃, nano-silica hybrid particles were obtained.
[0149] The method for preparing the modified calcium carbonate whiskers includes the following steps:
[0150] 100g of calcium carbonate whiskers (2μm in diameter, aspect ratio 30), 3g of titanate coupling agent, 2g of stearic acid and 1000mL of isopropanol were mixed and stirred at 400r / min and 50℃ for 1h for modification treatment. After filtration, washing with isopropanol and drying at 60℃, modified calcium carbonate whiskers were obtained.
[0151] Example 6
[0152] This embodiment provides a method for preparing a high-strength cross-linked polyethylene power cable, comprising the following steps:
[0153] Copper conductors are stranded together, and a cross-linked polyethylene insulation layer is extruded on the outside of the conductors. The insulation layer is then cross-linked in hot water at 90°C for 12 hours to obtain a primary cable.
[0154] 620g of high-density polyethylene (melt index 1.2g / 10min, density 0.950g / cm³) was used. 3 180g linear low-density polyethylene (melt index 2.0g / 10min, density 0.920g / cm³) 3 130g of modified basalt fiber, 70g of nano-silica hybrid particles, 70g of modified calcium carbonate whiskers, 50g of maleic anhydride-grafted polyethylene, 32g of vinyltrimethoxysilane, 13g of dicumyl peroxide, 6g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 6g of silicone masterbatch were mixed and then subjected to a mixing treatment at 650r / min and 70℃ for 20min to obtain a mixture.
[0155] The mixture is melt-granulated using a twin-screw extruder with zone temperatures of 165 / 170 / 175 / 175 / 170°C and a screw speed of 150 rpm. Then, an outer sheath is formed by extruding the primary cable's insulation layer using a single-screw extruder with zone temperatures of 145 / 150 / 155 / 155°C, a die temperature of 160°C, and a screw speed of 20 r / min. Finally, it undergoes cross-linking treatment in 90°C hot water for 12 hours to obtain a high-strength cross-linked polyethylene power cable.
[0156] The method for preparing the modified basalt fiber includes the following steps:
[0157] 100g of basalt fiber short filaments (10μm in diameter and 2mm in length) were mixed with 1200mL of γ-glycidoxypropyltrimethoxysilane aqueous solution (2% by mass). The mixture was stirred at 300r / min and 55℃ for 1.5h for coupling treatment, filtered, and dried at 60℃ to obtain the initial modified fiber.
[0158] The modified fiber was mixed with 450 mL of waterborne polyurethane emulsion (solid content of 15%), and then soaked in the mixture at 30°C for 30 min for coating treatment. After removal, it was dried at 70°C to obtain modified basalt fiber.
[0159] The preparation method of the nano-silica hybrid particles includes the following steps:
[0160] 100g of nano-silica (30nm particle size), 20g of γ-methacryloxypropyltrimethoxysilane and 1500mL of toluene were mixed and stirred at 300r / min and 80℃ for 4h under nitrogen protection. After centrifugation, the mixture was washed with toluene and dried at 60℃ to obtain functionalized nano-silica.
[0161] 100g of the functionalized nano-silica, 120g of methyl methacrylate monomer, 2g of azobisisobutyronitrile and 1200mL of toluene were mixed and grafted under nitrogen protection at 300r / min and 70℃ for 5h. After precipitation with methanol, washing and drying at 60℃, nano-silica hybrid particles were obtained.
[0162] The method for preparing the modified calcium carbonate whiskers includes the following steps:
[0163] 100g of calcium carbonate whiskers (diameter 1.2μm, aspect ratio 20), 2g of titanate coupling agent, 1g of stearic acid and 800mL of isopropanol were mixed and stirred at 300r / min and 45℃ for 1.5h for modification treatment. After filtration, washing with isopropanol and drying at 60℃, modified calcium carbonate whiskers were obtained.
[0164] Comparative Example 1
[0165] This comparative example provides a method for preparing a high-strength cross-linked polyethylene power cable. The difference from Example 6 is that ordinary basalt fiber chopped strands are used instead of modified basalt fiber, while the other raw materials and steps are the same.
[0166] Comparative Example 2
[0167] This comparative example provides a method for preparing a high-strength cross-linked polyethylene power cable. The difference from Example 6 is that ordinary calcium carbonate whiskers are used instead of modified calcium carbonate whiskers, while the other raw materials and steps are the same.
[0168] Comparative Example 3
[0169] This comparative example provides a method for preparing a high-strength cross-linked polyethylene power cable. The difference from Example 6 is that ordinary nano-silica is used instead of nano-silica hybrid particles, while the other raw materials and steps are the same.
[0170] Comparative Example 4
[0171] This comparative example provides a method for preparing a high-strength cross-linked polyethylene power cable. The difference from Example 6 is that vinyltrimethoxysilane and dicumyl peroxide are not added, while the other raw materials and steps are the same.
[0172] The performance of the high-strength cross-linked polyethylene power cables in Examples 1-6 and Comparative Examples 1-4 was tested, and the test results are shown in Table 1. Wherein:
[0173] Tensile strength and elongation at break tests: The outer sheath of the cables prepared in each embodiment and comparative example was stripped and cut into dumbbell-shaped specimens (gauge length 25 mm, width 6 mm). The specimens were clamped on an electronic universal testing machine and stretched uniformly along the longitudinal axis of the specimen at a tensile speed of 50 mm / min. The stress-strain curve was automatically recorded. The maximum tensile stress at the time of specimen breakage was read as the tensile strength (MPa). The percentage of the elongation of the gauge length at the time of specimen breakage relative to the original gauge length was read as the elongation at break (%). Five specimens were tested in each group, and the average value was taken.
[0174] Test of tensile strength retention rate after heat aging: The outer sheath sample is suspended in the heat aging test chamber and aged continuously at a constant temperature of 100℃ for 240h. After being taken out, it is placed at room temperature (23±2℃) for 16h to recover naturally. The tensile strength after aging is determined according to the above tensile strength test method. The tensile strength retention rate after heat aging (%) is calculated as the percentage of tensile strength after aging to tensile strength before aging. Five samples are tested in each group, and the average value is taken.
[0175] Test on elongation at break after heat aging: The outer sheath sample was suspended in a heat aging test chamber and aged continuously at a constant temperature of 100℃ for 240 hours. After being taken out, it was placed at room temperature (23±2℃) for 16 hours to recover naturally. The elongation at break after aging was measured according to the above elongation at break test method. The elongation at break after heat aging was calculated as the percentage of the elongation at break after aging to the elongation at break before aging. Five samples were tested in each group, and the average value was taken.
[0176] Density test: Cut the outer sheath sample into small pieces. Weigh the sample in air on an analytical balance. Then, completely immerse the sample in a beaker containing deionized water and weigh the apparent mass of the sample in water. Calculate the sample density (g / cm³) according to Archimedes' principle. Test 3 samples in each group and take the average value.
[0177] Abrasion resistance test: The outer sheath is cut into circular specimens with a diameter of 100 mm and fixed on the turntable of the Taber abrasion tester. An H-18 grinding wheel is selected, and a 500 g weight load is applied. The specimen is continuously rotated at a speed of 60 r / min for 1000 revolutions at room temperature. After the abrasion is completed, the mass of the specimen is weighed using an analytical balance. The mass difference before and after abrasion is taken as the wear mass loss (mg). The smaller the wear mass loss, the better the abrasion resistance. Three specimens are tested in each group, and the average value is taken.
[0178] High-temperature pressure test: The outer sheath is cut into flat specimens and placed in a high-temperature pressure test device. A constant pressure of 4 MPa is applied to the specimens under a constant temperature of 100℃ for 6 hours. After the pressure is released, the specimens are taken out and allowed to cool naturally to room temperature. The depth of the indentation on the specimen surface is measured with a microscope. The percentage of the indentation depth relative to the original thickness of the specimen is taken as the high-temperature pressure indentation depth (%). The smaller the indentation depth, the better the compressive strength. Three specimens are tested in each group, and the average value is taken.
[0179] Table 1 Performance Test Results
[0180] project Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Tensile strength (MPa) 42.5 44.8 40.2 46.3 43.8 45.6 32.5 35.8 33.2 28.5 Elongation at break (%) 385 352 428 338 405 368 295 312 278 355 Tensile strength retention rate after heat aging (%) 95.2 94.8 95.5 94.5 95.8 95.0 86.2 88.5 85.8 72.5 Elongation at break retention rate after heat aging (%) 92.8 91.5 93.2 90.8 93.5 92.2 78.5 82.2 76.8 62.5 <![CDATA[Density (g / cm 3 )]]> 1.06 1.07 1.05 1.08 1.06 1.07 1.04 1.05 1.05 1.03 Wear mass loss (mg) 6.8 5.9 7.2 5.5 6.2 5.8 12.5 10.8 11.2 15.8 High-temperature pressure indentation depth (%) 4.2 3.8 4.5 3.5 4.0 3.6 7.8 6.5 7.2 12.5
[0181] The high-strength cross-linked polyethylene power cables from Examples 1-6 and Comparative Examples 1-4 were tested for resistance to environmental stress cracking, low-temperature impact, and long-term creep. The test results are shown in Table 2. Among them:
[0182] Environmental stress cracking resistance (ESCR) test: The outer sheath is cut into rectangular strips. A 0.5 mm deep groove is made on the surface of the specimen with a blade along the transverse direction. The grooved specimen is bent into a U-shape and fixed on the specimen fixture with the grooved surface facing outwards at the maximum bending strain state. The fixture and the specimen are completely immersed in a test container containing a 10% Igepal CO-630 aqueous solution at a constant temperature of 50°C. The specimen is removed every 24 hours to observe whether there are visible cracks in the grooved area. The time taken when 50% of the specimens (i.e., the 5th out of 10 specimens) develop cracks is taken as the F50 value (h). The larger the F50 value, the better the environmental stress cracking resistance. 10 specimens are tested in each group.
[0183] Low-temperature impact test: Cut the outer sheath into rectangular sheet specimens and place them together with a 2kg drop hammer in a -40℃ low-temperature chamber for 4 hours to pre-treat them, so that both the specimens and the drop hammer reach a stable temperature of -40℃. After removal, immediately place the specimens on the impact test bench and let the 2kg drop hammer fall freely from a height of 200mm in the vertical direction to impact the specimen surface. Visually inspect the impact area of the specimens for cracks or damage. The percentage of specimens without cracks or damage is taken as the low-temperature impact pass rate (%). The higher the pass rate, the better the low-temperature toughness. 10 specimens are tested in each group.
[0184] Long-term creep test: The outer sheath is cut into dumbbell-shaped specimens (gauge length 25 mm, width 6 mm). Mark the two ends of the gauge length of the specimen and clamp it on the fixture of the creep testing machine. Apply a constant tensile stress of 10 MPa to the specimen at room temperature (23±2℃) for 1000 h. After loading, measure the elongation of the gauge length of the specimen. The percentage of elongation to the original gauge length is taken as the creep deformation rate (%). The smaller the creep deformation rate, the better the creep resistance. Three specimens are tested in each group and the average value is taken.
[0185] Heat shrinkage test: Cut the outer sheath into strips 100mm long and 10mm wide. Mark the two ends of the sample. The spacing between the marks is accurately measured and recorded as the initial length L0. Place the sample in a 150℃ constant temperature oven and let it sit freely (without external force constraints) for 1 hour. After that, take it out and let it cool naturally at room temperature to 23±2℃. Measure the length L1 between the marks on the sample again. Use (L0-L1) / L0×100% as the heat shrinkage rate (%). The smaller the heat shrinkage rate, the better the high-temperature dimensional stability of the material. Test 3 samples in each group and take the average value.
[0186] Table 2 Test Results
[0187] project ESCR F50(h) -40℃ low temperature impact pass rate (%) Creep deformation rate over 1000 hours (%) Heat shrinkage rate at 150℃ Example 1 680 100 2.8 0.8 Example 2 720 100 2.5 0.7 Example 3 650 100 3.0 0.9 Example 4 750 100 2.2 0.6 Example 5 700 100 2.6 0.8 Example 6 730 100 2.4 0.7 Comparative Example 1 320 80 5.8 1.5 Comparative Example 2 380 90 4.5 1.3 Comparative Example 3 280 70 6.2 1.6 Comparative Example 4 150 60 12.5 3.2
[0188] The technical solutions provided by the embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A high-strength cross-linked polyethylene power cable, characterized in that, It includes a conductor, a cross-linked polyethylene insulation layer extruded over the conductor, and an outer sheath extruded over the cross-linked polyethylene insulation layer, wherein the outer sheath, by weight, comprises the following raw materials: 50-70 parts high-density polyethylene, 15-30 parts linear low-density polyethylene, 8-15 parts modified basalt fiber, 5-10 parts nano-silica hybrid particles, 5-8 parts modified calcium carbonate whiskers, 2-4 parts vinyltrimethoxysilane, 0.8-1.5 parts dicumyl peroxide, 3-6 parts maleic anhydride-grafted polyethylene, 0.3-0.8 parts pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 0.5-1 parts silicone masterbatch; The high-density polyethylene has a melt index of 0.5~2.0 g / 10 min and a density of 0.945~0.955 g / cm³. 3 The linear low-density polyethylene has a melt index of 0.5~3.0 g / 10 min and a density of 0.918~0.925 g / cm³. 3 .
2. The high-strength cross-linked polyethylene power cable according to claim 1, characterized in that, The method for preparing the modified basalt fiber includes the following steps: Basalt fiber chopped strands and an aqueous solution of γ-glycidyl etheroxypropyltrimethoxysilane were mixed and coupled to obtain the initial modified fiber. The modified basalt fiber is obtained by mixing the pre-modified fiber with an aqueous polyurethane emulsion and then coating it.
3. The high-strength cross-linked polyethylene power cable according to claim 2, characterized in that, The mass-to-volume ratio of the basalt fiber chopped strands to the aqueous solution of γ-glycidoxypropyltrimethoxysilane is 1 g: (8~15) mL, and the mass concentration of the aqueous solution of γ-glycidoxypropyltrimethoxysilane is 1%~3%; and / or The basalt fiber chopped strands have a diameter of 5~15μm and a length of 1~3mm; and / or The coupling treatment is carried out under stirring conditions, wherein the stirring speed is 200~400 r / min, the temperature is 50~60℃, and the time is 1~2 h; and / or The mass-to-volume ratio of the modified fiber to the aqueous polyurethane emulsion is 1 g: (3~6) mL, and the solid content of the aqueous polyurethane emulsion is 10%~20%; and / or The coating treatment is performed at a temperature of 25-35°C for 20-40 minutes.
4. The high-strength cross-linked polyethylene power cable according to claim 1, characterized in that, The preparation method of the nano-silica hybrid particles includes the following steps: Nano-silica, γ-methacryloxypropyltrimethoxysilane and toluene were mixed and then silanized under a nitrogen protective atmosphere to obtain functionalized nano-silica. The functionalized nano-silica, methyl methacrylate monomer, azobisisobutyronitrile and toluene are mixed and grafted under a nitrogen protective atmosphere to obtain the nano-silica hybrid particles.
5. The high-strength cross-linked polyethylene power cable according to claim 4, characterized in that, The mass-to-volume ratio of the nano-silica, γ-methacryloyloxypropyltrimethoxysilane, and toluene is 1 g : (0.15~0.25) g : (10~20) mL; and / or The particle size of the nano-silica is 15~30nm; and / or The silanization treatment is carried out under stirring conditions, wherein the stirring speed is 200~400 r / min, the temperature is 70~90℃, and the time is 3~5 h; and / or The functionalized nano-silica, methyl methacrylate monomer, azobisisobutyronitrile, and toluene have a mass-to-volume ratio of 1 g : (0.8~1.5) g : (0.01~0.03) g : (8~15) mL; and / or The grafting treatment is carried out under stirring conditions, with a stirring speed of 200~400 r / min, a temperature of 65~75℃, and a time of 4~6 h.
6. The high-strength cross-linked polyethylene power cable according to claim 1, characterized in that, The method for preparing the modified calcium carbonate whiskers includes the following steps: Modified calcium carbonate whiskers are obtained by mixing calcium carbonate whiskers, titanate coupling agent, stearic acid and isopropanol and then modifying them.
7. The high-strength cross-linked polyethylene power cable according to claim 6, characterized in that, The calcium carbonate whiskers have a diameter of 0.5~2μm and an aspect ratio of 15~30; and / or The mass-to-volume ratio of the calcium carbonate whiskers, titanate coupling agent, stearic acid, and isopropanol is 1 g : (0.01~0.03) g : (0.005~0.02) g : (5~10) mL; and / or The modification treatment is carried out under stirring conditions, with a stirring speed of 200~400 r / min, a temperature of 40~50℃, and a time of 1~2 h.
8. The method for preparing the high-strength cross-linked polyethylene power cable according to any one of claims 1 to 7, characterized in that, Includes the following steps: The conductors are stranded together, and a cross-linked polyethylene insulation layer is extruded outside the conductors to perform cross-linking, thus obtaining the primary cable; High-density polyethylene, linear low-density polyethylene, modified basalt fiber, nano-silica hybrid particles, modified calcium carbonate whiskers, maleic anhydride-grafted polyethylene, vinyltrimethoxysilane, dicumyl peroxide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and silicone masterbatch are mixed and then subjected to a mixing treatment to obtain a mixture. The mixture is melted and granulated using a twin-screw extruder, and then extruded over the insulation layer using a single-screw extruder to form an outer sheath. After cross-linking treatment, a high-strength cross-linked polyethylene power cable is obtained.
9. The method for preparing a high-strength cross-linked polyethylene power cable according to claim 8, characterized in that, The mixing process is carried out under stirring conditions, wherein the stirring speed is 500~800 r / min, the temperature is 60~80℃, and the time is 15~25 min; and / or The temperature in each zone of the twin-screw extruder is 150~180℃, and the screw speed is 100~200rpm; and / or The temperature of each zone of the single-screw extruder is 140~165℃, the die temperature is 155~165℃, and the screw speed is 15~30 r / min; and / or The crosslinking treatment is performed at a temperature of 85-95°C for 8-16 hours.
10. The application of the high-strength cross-linked polyethylene power cable according to any one of claims 1 to 7 in the field of traction power supply.